Regulatory reduction of real estate financing by banks (Economic and Political Thought, 2019)
The recent financial crisis revealed an important link between the stabilityof the banking system and real estate lending. An aim of the article is topresent tools in the field of banking supervision as the factors that may limitthe supply of such loans. The research covered only instruments introducedto the EU legislation through the CRDIV/CRR package; then, the methodof comparative analysis has been applied to show the scope of implementationthereof in individual EEA states. The obtained results allow statingthat supervisory measures undertaken in relation to capital requirements arecharacterised by significant flexibility. However, a relatively limited numberof countries have decided to use them because of their potential side effects.
Keywords: banking supervision, capital requirements, real estate market, systemic risk